Unexpected pancytopenia: Dasatinib induced aplastic anemia in chronic myeloid leukemia. (January 2022) - Feld, Jonathan; Steinberg, Amir; El Jamal, Siraj M; Shapira, Ilan
Introduction: The use of TKIs in CML has dramatically altered the natural course of the disease and improved outcomes for patients. TKIs overall have a very favorable safety profile. Dasatinib, a second generation TKI, is commonly used as a first-line treatment option in CML. Case report: We describe the first two reported cases of first-line dasatinib induced aplastic anemia in CML. In both patients, pancytopenia occurred within one year of diagnosis/starting dasatinib. Both bone marrow biopsies showed hypocellularity with mild fibrosis and persistent BCR-Abl1 positivity. Management & outcome: Dose reduction was attempted without success in both patients. In one patient, multiple TKIs were trialed, while in the other, growth factor support was attempted; neither regimen was effective. Ultimately, the cytopenias associated with dasatinib were only resolved after immunosuppression in one patient and allogeneic stem cell transplant in the other patient. Discussion: Prior reports have shown that aplasia/aplastic anemia can rarely be associated with imatinib and nilotinib. Here we show that dasatinib can lead to this phenomenon as well. This diagnosis should be considered in patients with CML who unexpectedly develop cytopenias.